The Development of Music Media as Relaxation for Students Who are Carrying Out Final Projects (Thesis) - Akmal Sutja; Rully Andi Yaksa; Siti Amanah (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
This study aims to develop and prove that the music media as relaxation for students who are carrying out their final project (thesis) in the program study Guidance and Counseling FKIP Jambi University. This study uses a type of R D (Research Development) research, namely researching, designing, producing, testing, the validity of the products produced using the ADDIE model (Analysis Design Development Implementation and Evaluation). The population in this study amounted to forty-six people, and the sample was divided into three groups, including: the first, a individual groups of four people, the secend, a small groups of ten people, and the third, a large groups of thirty-two people. Data were analyzed in two ways, the first qualitative analysis to interpret the responses of experts, lecturers and students, and the secend quantitative analysis using the percentage formula. Based on the research results, it was concluded that: the first development of relaxation music media products is produced through five stages, that is Analysis, Design, Development, Implementation, and Evaluation, The secend The resulting product is declared suitable for use in providing relaxation music therapy for students who are carrying out their final assignments, the third Music media developed according to peers is in the "very good" category with a percentage of 90.4%, and the fourth The large group trial obtained an average percentage of 94% in the "very good" category.